DOP051 Shorter disease duration is associated with higher response rates to vedolizumab in Crohn's disease but not ulcerative colitis: a multi-centre consortium analysis. (16th January 2018) - Faleck, D; Winters, A; Chablaney, S; Shashi, P; Meserve, J; Weiss, A; Aniwan, S; Koliani-Pace, J L; Kochhar, G; Boland, B; Singh, S; Hirten, R; et al.
Abstract: Background: Crohn's disease (CD) patients with shorter duration of disease have higher response rates to tumour necrosis factor (TNF)-antagonists. Whether improved response in early CD is specific to TNF-antagonists is unknown. We aimed to evaluate response to vedolizumab (VDZ) in inflammatory bowel disease (IBD) patients stratified by disease duration. Methods: This was a review of a multi-centre, U.S. based consortium of CD and ulcerative colitis (UC) of VDZ treated patients stratified by disease duration: early (≤2 years) vs. late (>2 years). Using time-to-event analyses, we quantified and compared rates of remission: clinical (complete resolution of IBD-related symptoms), steroid-free (on steroids at baseline, tapered off, no repeat steroid-prescription for 4 weeks), and endoscopic (absence of ulcers or erosions) at 6 months between early and late CD and UC. Cox proportional hazards modelling identified predictors of treatment outcomes. Hazard ratios (HR) with 95% confidence intervals (CI) are reported, with a HR >1 indicating an increased probability of remission. Results: A total of 650 CD patients (58% female, median 37 years of age, 91% anti-TNF exposed, 63% ileocolonic involvement, 68% stricturing or penetrating disease complication history), and 437 UC patients (50% female, median 39 years of age, 67% anti-TNF exposed, 59% pancolitis), were included. Cumulative rates for clinical, steroid-free, and endoscopic remission with VDZ treatment were higher in CD patients with early disease (Table). A similar effect by duration was not seen in UC. On multivariable analysis, after adjusting for phenotype, CRP, albumin, severity, and prior TNF-antagonist exposure, CD patients with shorter duration were significantly more likely to achieve clinical (HR 1.66, 95% CI 1.06–2.59), steroid-free (HR 3.39, 95% CI 1.66–6.92), and endoscopic remission (HR 1.90, 95% CI 1.06–3.39) vs. CD patients with disease duration >2 years. Treatment response to VDZ in UC patients with shorter disease duration was not significantly different on univariable or multivariable analyses compared with UC patients with longer standing disease. Conclusions: CD patients with early disease (≤2 years) treated with VDZ were significantly more likely to achieve clinical, steroid-free, and endoscopic remission compared with those with disease of longer duration. Impact of disease duration on remission rates with VDZ was not seen in UC patients. Further studies are needed to understand whether early use of VDZ in CD improves longer-term outcomes and prevents disease-related complications.